A gestão democrática sob a ótica do dirigente escolar - Mercy Rodrigues Ligeiro (2007)
This paper analyzes the schools headmasters conception about democratic management in relation to its participation process in the schools daily life. It investigates how much the perception of the schools headmasters about the democratic management has favored, or not, the increase in participation spaces and processes for the school community, analyzing the aspects and limits for its effectiveness. The methodological approach used was a case study of two municipal public schools in Belo Horizonte - MG considering that this methodology allowed a closer contact with the reality of the investigated process. The main procedures used for collecting data were: observations; analysis of documents (such as department meetings reports and pedagogical proposal); unstructured interviews with teachers and employees; and semi-structured interviews with the schools headmaster. The data was categorized on a table in order to illustrate each case separately. In the last chapter, the results were presented in a comparative way considering the two case studies. The principle of democratic management in the current educational legislation has imposed to the educational institutions a new format in which labor organizes itself, with the schools community participation taking place through school councils. Thus, school management becomes more decentralized which demands from the schools headmasters a new posture in the administration of the educative institution. This inquiry reveals that, in the schools headmasters point of view, school management is a complex and dichotomical process. At the same time it favors the democratization of education, with the community playing a larger role in the decision-making process on schools demands, these characteristics reflect the boundaries and limitations with which the headmaster has to conduct the schools administration. The significance of this study is in its attempt to contribute to the current discussions on educational politics and the relationship established between State and School in order to guarantee more autonomy to the educational facilities.